口腔扁平上皮癌におけるSCC 抗原の有用性についての検討 - 石上, 享嗣; 丹沢, 秀樹; 鵜澤, 一弘; 小越, 健次; 佐久間, 健太郎; 椎葉, 正史; 西尾, 可苗; 伏見, 一章; 秋葉, 正一; 肥後, 盛洋 (日本口腔外科学会雑誌, 2014)
To evaluate the usefulness of squamous cell carcinoma　（SCC） antigen for screening, prognosis, monitoring the response to surgical treatment, and early detection of recurrence and metastases from oral squamous cell carcinoma　（OSCC）, we investigated the time course of serum levels of SCC antigen in 156 patients with OSCC. Elevated serum SCC antigen levels were detected in 35 of the 156 patients with OSCC. Preoperative positive rates were low　（22%）. The higher the serum SCC antigen level, the larger was the primary tumor, and the clinical stage and cervical lymph-node metastasis were also more advanced. In patients who tested positive for serum SCC antigen before operation, the serum SCC antigen levels significantly declined after surgery. The SCC antigen level in the recurrent or metastatic group was significantly higher than that in the non-recurrent and non-metastatic group. Receiver operating characteristic　（ROC） curve analysis identified the optimal cut-off value　（1.34 ng/mL） of the preoperative serum SCC antigen to predict recurrence or metastasis of OSCC. The SCC antigen level immediately before the detection of recurrence or metastasis was significantly higher than the mean value after surgery. The optimal cut-off value　（1.40 ng/mL） of the postoperative serum SCC antigen level for suspecting recurrence or metastasis of OSCC was identified by ROC curve analysis. Our results suggested that the SCC antigen level is related to an increase in tumor volume, metastasis to cervical lymph nodes, and clinical stage. SCC antigen might be a useful prognostic factor. The SCC antigen level might be a useful for evaluating the efficacy of treatments in SCC antigen-positive cases and may facilitate the early detection of recurrence, metastasis, or both. However, because the clinical value of serum SCC antigen as a screening factor for OSCC is low, it might be an auxiliary tool for the screening of OSCC.